Chemical Examination of the Seeds of Cassia tora - Singhal, Amita (Asian Journal of Chemistry, 2016)
The carbohydrates and proteins have been analyzed from the seeds of Cassia tora. The seeds having high nutritional properties are useful in cattle feed industries.